0
$\begingroup$

Suppose we have a Lagrangian function $$L(\lambda, q) = \sum_{i=1}^{n}q(i)[\log\pi(u_i)+\log U(r_i) - \log q(i) + \lambda] - \lambda.$$

By using Lagrange multiplier we can find optimal $q(j)$.

The solution is $q(j) = \frac{\pi(u_j)U(r_j)}{\sum_{i=1}^{n}\pi(u_i)U(r_i)}$.

But it is quite strange to me, since by the standard procedure, we compute gradients $\frac{\partial L}{\partial \lambda}, \frac{\partial L}{\partial q}$, I got

$\begin{align} \frac{\partial L}{\partial \lambda} &= \big[\sum_{i=1}^{n}q(i)\big] - 1 = 0\\ \frac{\partial L}{\partial q(j)} &= \log\pi(u_j) + \log U(r_j) - \log q(j) - 1 + \lambda = 0 \end{align}$

Question: Then it is hard for me to continue, because it does not lead to the solution above.

Note: Here $q(i)$ is a probability distribution i.e. the constraint part. And $\pi(\cdot), U(\cdot)$ are just some functions depending on each iteration $i$

$\endgroup$
1
$\begingroup$

From

$$\frac{\partial L}{\partial q(j)}=0$$

We have $$\lambda-1 = \log \frac{q(j)}{U(r_j)\pi(u_j)}$$

which is equivalent to $$\exp(\lambda-1) = \frac{q(j)}{U(r_j)\pi(u_j)}$$

That is regardless of value of $j$, $\frac{q(j)}{U(r_j)\pi(u_j)}$ is a positive constant, or we can say that $q(j)$ is proportional to $U(r_j) \pi (u_j)$.

Also, we know that $q(j)$ sums to $1$ and they are non-negative.

Hence, $$q(j)=\frac{\pi(u_j)U(r_j)}{\sum_{i=1}^n\pi(u_i)U(r_i)}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.